THE CHANGE OF AGROCHEMICAL CHARACTERISTICS OF SOD-PODZOLIC SOIL WHEN USING ORGANIC FERMENTED FERTILIZERS - Гаврилюк, В. А.; Валецька, О. В. (Scientific Progress & Innovations, 2014)
The paper elucidates the main aspects of soil productivity increase through the use of organic and organo-mineral fertilizers of different composition. The results of field studies as well as of laboratory and agrochemical analyses below suggest that the application of organic fermented fertilizer (OFF) in the crop rotation link potato - oat - yellow lupine enhances the nutritive regime of sod-podzolic soil. We found that when applying 15 t/ha of OFF, which is equivalent to 30 t/ha of manure in terms of its nitrogen content, even during the second year of aftereffect there are no degradation processes. Thus, such fertilizer rate can be recommended for production considering the agrochemical cal perspective.